(3GdHQgGf aj CSQGQ GdejRGfs - (3GdLdOcj, YR GdOjf, Ydj Hf eMeO Hf CjOeQ, J HYO (B742 (3g`s
(3ChdgG (B:s
(3hcGf EPG MVQ dOQS GMceI hHGOQ CQSWh WGdjS HGdMVhQ bHd GdfGS Jcde acGf jJcde eYg heG Ydjg Ef MVQ GdfGS Ce de jMVQhG ade jcf YfOg GdfGS EdG s
(3BNQgG (B:s
(3Ke bGdJ GdedcI bdhHWQI (B: (3de JPcQhf GdefGSHI aj GdaYd hGdGfaYGd abGdhG(B: (3CeG gPG fUfg Yf GdeGA hgh CjVG jfGSH GdLSO GdcQje dCf GdCQV dG JCcdg GfJgi GdLRA GdKGfj hjdjg HbjI eHGMK GdedcI bdhHWQI aj GdLRA GdKGdK s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\5s
(3cTa GdXfhf (B1\241s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs